A Re-Designed Efficient Charcoal Stove. - Mwesigwa, Lourdel (Kabale University, 2025)
The study aimed to design a charcoal stove that optimizes energy from the cold start phase, hot start phase, and after cooking for food warming purposes. The study was based on two specific objectives to design a charcoal stove that utilizes fuel efficiently through high conductivity and heat loss prevention mechanisms and to add high heat retention features/accessories to the stove much longer after active cooking has stopped for food warming purposes. It was found that after 4 test runs of the water boiling test; the re-designed efficient charcoal stove had a mean thermal efficiency of 30.3%. This means that 30.3% of the total energy produced by the fuel is used to boil water in the saucepan. Based on its water boiling test results, 76.5% fuel use reduction was achieved over the baseline ceramic charcoal stove. This was attributed to the thermal retention storage properties of steel ball bearings and the heat retention balls. The ceramic covering/ insulation significantly improved the stove’s thermal efficiency by minimizing heat losses. The Re-designed efficient charcoal cooking stove was designed and fabricated using readily available materials like clay, ball bearings, and ceramic tiles. The performance standard and property of this stove showed a substantial improvement in technology and can lessen the pressure put on household incomes and forestry resources. However, further studies including particulate matter(PM) and carbon emissions are recommended for future design improvements to suit general public safety and health standards. Studies on the use of other forms of fuel like briquettes, wood chippings, food peelings, and agricultural harvest wastes could also be conducted to establish fuel alternatives to charcoal.